Subtypes of batterers in treatment: empirical support for a distinction between type I, type II and type III. - José Luis Graña; Natalia Redondo; Marina J Muñoz-Rivas; Arthur L Cantos (PLoS ONE, 2014)
This study explores the existence of different types of batterers in a sample of 266 men who had been court referred for intimate partner violence. The data collected in the assessment that have been used to perform a hierarchical and a two-step cluster analysis fall into three areas: aggression towards the partner, general aggression and presence of psychopathology and personality traits, more specifically, alcohol use, borderline and antisocial personality traits, psychopathy traits, state anger and trait anger, anger expression and control, anger, hostility, and, finally, impulsivity. The results show a typology consisting of 3 types of batterers on the basis of violence level and psychopathology: low (65%), moderate (27.8%) and high (7.1%). This study provides empirical support for the development of batterer typologies. These typologies will help achieve early detection of different types of batterers, allowing us to tailor interventions on the basis of the needs of each of the types.